PENGARUH ARUS KAS OPERASI, ARUS KAS INVESTASI, ARUS KAS PENDANAAN, LABA KOTOR DAN SIZE PERUSAHAAN TERHADAP RETURN SAHAM PERUSAHAAN (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2011-2013) - Wahid Fadoli, 10.05.52.0084; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2014)
This study aims to examine and analyze the effect of operating cash flow, investment cash flow, cash flow financing, the companys gross profit and size on stock returns of the company. The population in this study are stock companies listed in Indonesia Stock Exchange during 2011-2013. Sampling technique in this study is the use of purposive sampling. The data analysis technique used is multiple linear regression analysis. Based on the test results it can be concluded that: Operating cash flow is not a significant negative effect on stock returns. Cash flow investing significant positive effect on stock returns. Cash flow financing is not significant positive effect on stock returns. Gross profit significantly positive effect on stock returns. Size company is not significant positive effect on stock returns. Keywords: cash flow from operations, investment cash flow, cash flow financing, gross profit, company size and stock return